Microbial uptake of nitrogen and carbon from the water column by litter‐associated microbes differs among litter species. (17th March 2020) - Bastias, Elliot; Ribot, Miquel; Bernal, Susana; Sabater, Francesc; Martí, Eugènia
Abstract: Addition of isotopically labeled dissolved forms of nitrogen (N) and carbon (C) in streams has revealed that microbes associated with leaf litter can assimilate solutes from the water column. However, whether this assimilation varies among leaf litter species and at different decomposition stages is still largely unknown. Here, we explore differences in the uptake of NH4 ‐N and acetate from water column among leaf litter of five riparian tree species at five different times of decomposition. To do so, we conducted a 24 h addition of 15 N‐NH4 and 13 C‐acetate at constant rate to estimate the microbial uptake of these solutes from the water column. We measured microbial cellobiohydrolase activity and decomposition rates ( k ) associated with each leaf litter type to examine their influence on NH4 ‐N and acetate uptake. We found that mass specific N‐uptake ( μ g N mg N −1 d −1 ) was relatively constant during leaf litter decomposition whereas mass specific C‐uptake (mg C g C −1 d −1 ) increased over time. Among leaf litter species, cumulative values of N‐uptake during the study period were negatively related to leaf litter k whereas cumulative values of C‐uptake were positively related to k . Our study indicates that leaf litter species and their decomposition stage are important for understanding the reliance of leaf‐associated microbes on dissolved inorganic nitrogen and dissolved organic carbon from the water column.